SITOTOXIC TESTS OF SOME MONO COMPONENTS OF COCON HYDROXES ON CANCER CELL LINE T47D - Retno Arianingrum; Indyah Sulistyo Arty; Sri Atun (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2011)
The aim of this research was to study cytotocix activity from some mono para hydroxy compounds (MPHC) i.e. MPHC A, MHPC B, MPHC MPHC D, and MPHC E against T47D cancer cell lines. Those compounds were synthesized from benzaldehyde derivatives and acetofenon derivates through cross aldol reaction under acid condition. Separation and purification of these compounds were conducted by recrystallization technique using suitable eluent. Identification and structure elucidation was done by comparing the data of thin-layer chromatography (TLC) with marker (compounds that have been found previously), and also used the data of IR spectrum. Each compound then was performed cytotoxicity test by in vitro against T47D cells using MTT assay. Observation of cell morphological changes was observed using phase contrast microscopy. The results showed that the compound MPHC A, MPHC B, MPHC C, and MPHC D had cytotoxic activity against T47D cancer cell line, while the compound MPHK E did not have cytotoxic activity. The highest toxicity was MPHK A with LC50= 66.44 Pg/mL. The presence of hydroxyl groups contributed to the enhancement of cytotoxic effect.